Pengembangan Media Pembelajaran Scrapbook Untuk Keterampilan Membaca - Pratitis Kusumaning Asih; Shanty Hawanti; Okto Wijayanti (Indonesian Journal of Primary Education, 2020)
Abstract Learning skill is a form of language skill that is important for students to master. To adept reading, students ought to go through a fun reading learning process. One of the way to achieve it is by using learning media that is interesting and is able to help students read easier. This research is a research and development to develop a learning media for reading skill in form of a scrapbook. The background of this research is the lack of reading skill of 2nd grade students in Public Primary School 1 Majakerta with 20 students.  The design used for this research and development was referred to 4D stages that consist of Define, Design, Develop, and Disseminate. Based on result of expert validation, developed scrapbook as learning media is stated as decent to be used in learning of reading skill. After undergone through improvements, the final product has shown product appropriateness. The scrapbook learning media is declared to be suitable for use after it is produced. The result of teachers' response shows positive response to the final product as well, which means they state that the media is able to be used to help them teach learning skills to their students. Abstrak Keterampilan membaca merupakan satu bentuk keterampilan berbahasa yang penting dikuasai oleh siswa. Untuk terampil membaca, siswa harus mengalami proses belajar membaca yang menyenangkan, salah satunya adalah dengan menggunakan media berlatih membaca yang menarik dan mampu membantu siswa lebih mudah membaca. Penelitian ini merupakan penelitian dan pengembangan (RnD) yang bertujuan untuk mengembangkan media pembelajaran keterampilan membaca berbentuk scrapbook. Pengembangan media ini rendahnya keterampilan membaca siswa kelas II di SD Negeri 1 Majakerta dengan siswa berjumlah 20 siswa.  Desain penelitian dan pengembangan yang digunakan adalah mengacu pada tahapan 4-D yaitu Define (Pendefinisian), Design (Perancangan), (Pengembangan) dan Disseminate (Penyebaran). Berdasarkan hasil validasi ahli media scrapbook yang dikembangkan dinyatakan layak untuk pembelajaran keterampilan membaca. Setelah mengalami perbaikan sampai pada produk akhir menunjukkan kelayan produk. Media pembelajaran scrapbook dinyatakan layak digunakan setelah itu dilakukan produksi. Hasil respon guru juga menunjukkan respon positif terhadap media yang dikembangkan, artinya guru menyatakan bahwa media dapat digunakan untuk membantu mengajarkan keterampilan membaca siswa.